A Mediastinal Mass Presenting With Unilateral Periscapular and Arm Pain. Issue 6 (7th January 2014) - McCormick, Zack; Bouffard, Karina J.; Neudorf, Daniel; Casey, Ellen
Abstract : We describe a case of a patient with mediastinal lymphoma who presented with arm and scapular pain, which is an atypical referral pattern for pain originating from the mediastinum. We use this case as a platform to discuss mediastinal pain referral patterns and the importance of maintaining a broad differential diagnosis of arm and scapular pain, especially when symptoms atypical of pure neuromusculoskeletal structural disease are present.